Optimizing SLiMS 8 Acacia to Improve Service Quality: A Case Study at UIN Fatmawati Sukarno Bengkulu Library - Muhammad Aziz Fikri; Siti Rohaya; Basinun Basinun; Sri Yuliani (Journal of Social Work and Science Education, 2026)
This study analyzed how to optimize SLiMS 8 Acacia in improving the quality of library services at Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu and analyze the factors that hinder the optimization. This research is qualitative research using interview, observation and documentation methods. The results show that the optimization of the use of SLiMS 8 Acacia has been carried out through the establishment of clear service objectives, the development of additional features, and the integration of the system with user needs. These efforts have been proven to improve the quality of library services, especially in terms of ease of access to information, efficiency of collection management, and improvement of users' digital literacy. In addition, SLiMS-based services are considered quite good when viewed from five service quality indicators, namely appearance, reliability, responsiveness, certainty, and empathy for the needs of the librarian. Some of the obstacles faced include limited technology infrastructure, lack of competent human resources in technical/IT terms, uneven levels of technology literacy among users, and technical obstacles related to data migration and integration from previous systems.